2021
DOI: 10.1021/acs.chemrestox.1c00094
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine-Conjugated Nitroxides Are Efficacious Inhibitors of Oxidative Reactions Catalyzed by Endothelial-Localized Myeloperoxidase

Abstract: The heme enzyme myeloperoxidase (MPO) is a key mediator of endothelial dysfunction and a therapeutic target in cardiovascular disease. During inflammation, MPO released by circulating leukocytes is internalized by endothelial cells and transcytosed into the subendothelial extracellular matrix of diseased vessels. At this site, MPO mediates endothelial dysfunction by catalytically consuming nitric oxide (NO) and producing reactive oxidants, hypochlorous acid (HOCl) and the nitrogen dioxide radical (•NO2). Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
1
0
0
Order By: Relevance
“…This formation of compound II contains a ferryl iron-oxygen moiety, and superoxide anion radicals can convert ferric MPO into compound III, a mixed ferric-superoxide/ferrousdioxygen complex. Interestingly, a negative feedback loop of H 2 O 2 on MPO was shown in vitro [13], and similar findings were observed in the presence of nitroxide [14,15]. During an immune response, a mixture of reactive species, including H 2 O 2 , is present [16,17], supporting the hypothesis of inhibiting and controlling MPO for homeostasis.…”
Section: Introductionsupporting
confidence: 67%
“…This formation of compound II contains a ferryl iron-oxygen moiety, and superoxide anion radicals can convert ferric MPO into compound III, a mixed ferric-superoxide/ferrousdioxygen complex. Interestingly, a negative feedback loop of H 2 O 2 on MPO was shown in vitro [13], and similar findings were observed in the presence of nitroxide [14,15]. During an immune response, a mixture of reactive species, including H 2 O 2 , is present [16,17], supporting the hypothesis of inhibiting and controlling MPO for homeostasis.…”
Section: Introductionsupporting
confidence: 67%
“…Par-ticularly, TEMPO exerts a multifaceted antioxidant efficacy by inhibiting myeloperoxidase, a heme peroxidase enzyme impaired in inflammatory diseases, and directly counteracting oxidant species. In this view, Maiocchi et al exploited the TEMPO nucleus to attach different polyamines in order to increase its bioavailability and antioxidant potency [114]. Notably, Put-TEMPO hybrid 70 (Figure 20) achieved one of the highest cellular uptakes, which allowed it to retain efficient inhibition of cellular myeloperoxidase activities such as chlorination, H 2 O 2 consumption, HOCl production, protein nitration and NO oxidation [114].…”
Section: Antioxidantmentioning
confidence: 99%
“…In this view, Maiocchi et al exploited the TEMPO nucleus to attach different polyamines in order to increase its bioavailability and antioxidant potency [114]. Notably, Put-TEMPO hybrid 70 (Figure 20) achieved one of the highest cellular uptakes, which allowed it to retain efficient inhibition of cellular myeloperoxidase activities such as chlorination, H 2 O 2 consumption, HOCl production, protein nitration and NO oxidation [114]. Minoxidil belongs to a similar nitrone family and is an antihypertensive agent with antinflammatory properties.…”
Section: Antioxidantmentioning
confidence: 99%
See 1 more Smart Citation
“…MPO binds to lipoproteins such as LDL [148][149][150] (where apoB-100, the major apolipoprotein of LDL, and respective lipid species represent major targets for HOCl attack [151,152]) and high-density lipoprotein (HDL) [153][154][155] (quite heterogenous lipoprotein particles varying in density, size, electrophoretic mobility, and protein and lipid composition; for a review, see [156]). Although electron microscopy studies originally revealed limited binding and internalization of MPO (compared to EPO) to inflammatory cells [157], ongoing studies clearly underscore the adverse oxidative reactions of endothelial-localized MPO [158] as well as endothelial-transcytosed MPO [109] leading to targeted subendothelial matrix oxidation of proteins [159][160][161][162][163][164] via MPO-mediated nitration and/or chlorination; the latter reaction could by suppressed by SCN − and nitrite (NO 2 − ) [162].…”
Section: Important Reactions Of (Pseudo)hypohalous Acids and Targets ...mentioning
confidence: 99%